1992
DOI: 10.1104/pp.100.2.820
|View full text |Cite
|
Sign up to set email alerts
|

Normal Growth of Transgenic Tobacco Plants in the Absence of Cytosolic Pyruvate Kinase

Abstract: The coding sequence of the cytosolic isozyme of potato tuber pyruvate kinase (PK) was attached to the transit peptide of the small subunit of pea ribulose-1,5-bisphosphate carboxylase oxygenase and placed under the control of the cauliflower mosaic virus 35S promoter. This construct was transformed into Nicotiana tabacum. Unexpectedly, two primary transformants were recovered in which PK activity in leaves was greatly reduced. The reduction in PK activity appeared to result from the complete absence of the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 32 publications
3
19
0
1
Order By: Relevance
“…At the same time, increased PEP and pyruvate levels were reported for the mutant, which is consistent with the idea of swelling of PEP levels in response to a reduction in PKp (Andre et al, 2007). Similar to PKp mutations, in PKc-deficient tobacco (Nicotiana tabacum) plants, the level of PEP in leaves was found to be significantly increased as compared with the wild type (Gottlob-McHugh et al, 1992).…”
Section: Control Of Carbon Partitioning Between Lipid and Starchsupporting
confidence: 73%
“…At the same time, increased PEP and pyruvate levels were reported for the mutant, which is consistent with the idea of swelling of PEP levels in response to a reduction in PKp (Andre et al, 2007). Similar to PKp mutations, in PKc-deficient tobacco (Nicotiana tabacum) plants, the level of PEP in leaves was found to be significantly increased as compared with the wild type (Gottlob-McHugh et al, 1992).…”
Section: Control Of Carbon Partitioning Between Lipid and Starchsupporting
confidence: 73%
“…A previous study demonstrated that transgenic tobacco plants lacking the expression of cytosolic pyruvate kinase showed basically normal growth (Gottlob-McHugh et al, 1992). However, in a later report, inhibition of root growth and a decrease in the export of fixed carbon from the leaves to other organs were observed when these transgenic tobacco plants were cultivated under low light intensities (Knowles et al, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…Plant Number cosuppression of beta-I, 3-glucanase genes (de Carvalho et al 1992), pyruvate kinase genes (Gottlob-McHugh et al 1992), nitrate reductase genes (Dorlhac de Borne et al 1994), and acetohydroxyacid synthase (Brandle et al 1995) genes.…”
Section: Instability Of Transgene Expressionmentioning
confidence: 99%